2005
DOI: 10.1002/cbdv.200590086
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial Physalins fromPhysalis minima

Abstract: Three new physalins (1-3) and a new withanolide 7 have been isolated from the whole plant of Physalis minima, along with three known physalins: physalin H (4), isophysalin B (5), and 5beta,6beta-epoxyphysalin B (6). Their structures were deduced on the basis of in-depth spectroscopic analyses. Compounds 1-6 showed significant in vitro leishmanicidal activities (0.92-19.4 microg/ml) against promastigotes of Leishmania major.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 26 publications
0
41
0
Order By: Relevance
“…12.2 ± 1.5 14.0 ± 0.7 32.4 ± 1.2 -E. faecalis 9.0 ± 1.9 9.8 ± 1.9 21.6 ± 1.1 -B. subtilis 11.2 ± 1.9 13.8 ± 1.3 30.4 ± 1.1 -B. cereus 14.4 ± 0.5 14.8 ± 1.5 27.2 ± 2.4 -Gram(-) bacteria E. coli 6.0 ± 2.4 8.2 ± 1.8 28.4 ± 1.1 -P. aeruginosa 7.6 ± 1.1 10.2 ± 2.6 25.0 ± 1.9 -E. cloacae 9.8 ± 2.7 10.6 ± 0.5 22.8 ± 3.7 -K. pneumoniae 7.8 ± 2.0 7.8 ± 0.4 25.0 ± 2.5 -P. vulgaris 6.0 ± 1.0 7.8 ± 1.3 22.0 ± 1.6 -Fungi C. albicans -6.2 ± 0.8 -23.8 ± 0.8 C. krusei -3.8 ± 0.4 -26.6 ± 1.5 C. glabrata -6.2 ± 0.4 -29.2 ± 1.9 C. tropicalis ---21.2 ± 1.9 C. paraphilosis ---22.6 ± 2.5 a In the literature, there is no report about the antioxidant activity of physalins or the extracts of Physalis species. Our report is the first for physalin D. Previous phytochemical studies on the aerial parts of Physalis plants have led to the identification of physalins, which are believed to be the bioactive compounds of the genus Physalis (Januário et al, 2002;Dos Santos et al, 2003;Wu et al, 2004;Choudhary et al, 2005;Lee & Houghton, 2005;Magalhaes et al, 2006;Damu et al, 2007;Castro et al, 2008). However, there is relatively little information in the literature regarding the steroid content of the calyces of Physalis species (Dinan et al, 1997;Qiu et al, 2008).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…12.2 ± 1.5 14.0 ± 0.7 32.4 ± 1.2 -E. faecalis 9.0 ± 1.9 9.8 ± 1.9 21.6 ± 1.1 -B. subtilis 11.2 ± 1.9 13.8 ± 1.3 30.4 ± 1.1 -B. cereus 14.4 ± 0.5 14.8 ± 1.5 27.2 ± 2.4 -Gram(-) bacteria E. coli 6.0 ± 2.4 8.2 ± 1.8 28.4 ± 1.1 -P. aeruginosa 7.6 ± 1.1 10.2 ± 2.6 25.0 ± 1.9 -E. cloacae 9.8 ± 2.7 10.6 ± 0.5 22.8 ± 3.7 -K. pneumoniae 7.8 ± 2.0 7.8 ± 0.4 25.0 ± 2.5 -P. vulgaris 6.0 ± 1.0 7.8 ± 1.3 22.0 ± 1.6 -Fungi C. albicans -6.2 ± 0.8 -23.8 ± 0.8 C. krusei -3.8 ± 0.4 -26.6 ± 1.5 C. glabrata -6.2 ± 0.4 -29.2 ± 1.9 C. tropicalis ---21.2 ± 1.9 C. paraphilosis ---22.6 ± 2.5 a In the literature, there is no report about the antioxidant activity of physalins or the extracts of Physalis species. Our report is the first for physalin D. Previous phytochemical studies on the aerial parts of Physalis plants have led to the identification of physalins, which are believed to be the bioactive compounds of the genus Physalis (Januário et al, 2002;Dos Santos et al, 2003;Wu et al, 2004;Choudhary et al, 2005;Lee & Houghton, 2005;Magalhaes et al, 2006;Damu et al, 2007;Castro et al, 2008). However, there is relatively little information in the literature regarding the steroid content of the calyces of Physalis species (Dinan et al, 1997;Qiu et al, 2008).…”
Section: Resultsmentioning
confidence: 82%
“…Previous studies have focused on the isolation and characterization of secondary metabolites, whereas it has been demonstrated that some of the extracts or active principles obtained from Physalis species have a broad spectrum of biological activities, including antileukemic, antitumor, immunomodulator, cytotoxic, antimycobacterial, antimicrobial, molluscicidal, antihepatoma, and antinociceptive activities in recent studies (Chiang et al, 1992a(Chiang et al, , 1992bJanuário et al, 2002;Shim et al, 2002;Su et al, 2002;Dos Santos et al, 2003;Soares et al, 2003;Wu et al, 2004;Choudhary et al, 2005;Lee & Houghton, 2005;Silva et al, 2005;Bastos et al, 2006;Magalhaes et al, 2006;Damu et al, 2007;Castro et al, 2008). It has been previously reported that the crude extract (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…D 16 -Withanolides with oxygen substituents at C-14 and C-15 have the appropriate functionalities for cleavage of the 13,14-bond, and the occurrence of such withanolides in physalin-rich plants strongly suggests that they are either precursors or shunt products in the biosynthesis of physalins (59). A D 14 -withanolide, 107, was also reported from P. minima collected in Pakistan (60). (115), and a 14a,20-epoxywithanolide (116) (65).…”
Section: C-14 C-17 and C-20 Hydroxylated Withanolides And Related Cmentioning
confidence: 94%
“…while physalins 298, 300, 301, physalin H (312), isophysalin B (474), and 5b,6b-epoxyphysalin B (502) also had significant activity. The 3-methoxy derivative physalin U (304) and withanolide 107 with an unmodified skeleton were only marginally active (60,145). Removal of the C-6 hydroxy group of physalin H (312) to give either the dehydration product 473 or the deoxygenated physalin 475 (see Sect.…”
Section: Leishmanicidal Activitymentioning
confidence: 99%
“…Previous studies have shown that physalin H, isophysalin B, 5 beta, 6 beta-epoxyphysalin B and others isolated of Physalis minima have in vitro antileishmanial activitiy against promastigotes of L. major (Choudhary et al, 2005;Choudhary et al, 2007). In the present study we demonstrated the antileishmanial activity of physalins B, F, and G isolated from Physalis angulata in vitro in axenic cultures of different Leishmania species, including L. amazonensis, L. braziliensis, L. chagasi (New World), and L. major (Old World).…”
Section: Discussionmentioning
confidence: 99%